Study of Clinical Pro?le of Neonatal Seizures in Level III NICU - P. Anil Kumar; V. Ramgopal Rao (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: During the neonatal age, seizures are the most distinctive sign of neurological disease. Convulsive symptoms are the most promi- nent forms of neonatal neurological disorders. The goal of this research was to have a better view of the epidemiology, etiology, incidence, forms and mortality of neonatal seizures in our hospital. This research was undertaken to evaluate the prevalence, forms of neonatal seizures, etiology, occurrence period and correlation with etiology, and to establish the mortality correlated with neonatal seizures. For research the etiology and its etiological connection, the occurrence of neonatal seizures. Subjects and Methods: A comprehensive history was collected for the antenatal, natal, postnatal and family history. Age of initiation, form, duration and amount of seizures, consciousness before and after the seizures were taken. Comprehensive neonate examination was performed after detailed history. Relevant investigations were carried out depending upon clinical presentation. Results: In our analysis of 200 neonatal seizures, 194 had one of the four classically identified neonatal seizures. Multifocal clonic seizures were among the most common type of seizures 36% (72 cases) followed by subtle 27% (54 cases), GTS 26% (52 cases), Myoclonic 7% (15 cases), mixed type of seizures 3% (6 cases) and focal clonic seizures 1% (2 cases). Conclusion: Because neonatal seizures are most frequently due to birth asphyxia, better antenatal and perinatal care reduces birth asphyxia and if mothers are identified as high-risk. The impact of neonatal seizures is thereby minimized. Subtle seizures are the most frequent form of psychiatric seizure; thus, close monitoring of newborns at risk is important.